Role of Insect Pollinators in Crop Production and Ecosystem - Sahani, Shrawan Kumar; Chandra , Khushboo; Girase , Indrajitsingh P.; Saikanth , D. R. K.; Singh , Sarvendra; Swamy , G. Narayana; Singh , Bal Veer (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Pollinators, particularly insects, play an indispensable role in ensuring the health of terrestrial ecosystems and in bolstering agricultural productivity. Their symbiotic relationship with plants has evolved over millennia, resulting in co-adaptations that facilitate the reproductive success of many plant species. This review sheds light on the multifaceted interactions between insect pollinators and plants, emphasizing their contributions not only in crop production but also in maintaining broader ecosystem services. The importance of insect pollinators, such as bees, butterflies, beetles, and flies, among others, is highlighted by their direct influence on the yield and quality of many crops. Notably, global agricultural sectors like fruits (e.g., apples and berries) and nuts (e.g., almonds) heavily depend on these insects for pollination. In economic terms, pollinators contribute substantially, with their decline potentially resulting in significant economic losses globally. Beyond agriculture, insect pollinators play a role in numerous ecosystem services. They aid in seed dispersal, ensuring gene flow and maintaining genetic diversity within plant populations. They act as crucial nodes in the food web, serving as prey for a plethora of species. They also indirectly support soil health by promoting the decomposition of plant matter, which enriches soil fertility and structure. Despite their importance, pollinators are under threat from various anthropogenic factors. Pesticides, habitat destruction, and climate change have been identified as primary drivers behind the decline of many pollinator species. Disease outbreaks and the proliferation of parasites further compound these challenges. Addressing these threats requires integrated conservation strategies. Practices like integrated pest management can minimize pesticide impact, while creating and maintaining pollinator habitats in agricultural and urban landscapes can provide refuges for these insects. Breeding programs targeting disease and parasite resistance and global collaborative efforts can further bolster pollinator populations. Investing in their conservation is not just an ecological imperative but also a socioeconomic one, ensuring food security for the growing global population. Emerging research avenues, such as genomic studies on pollinators, offer potential solutions and deeper insights into their resilience and adaptability. As the world grapples with escalating environmental challenges, understanding and supporting insect pollinators is paramount for a sustainable future.Insect pollinators